2005
DOI: 10.1111/j.1523-5378.2005.00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cranberry Juice on Helicobacter pylori Infection: a Double‐Blind, Randomized Placebo‐Controlled Trial

Abstract: Regular consumption of cranberry juice can suppress H. pylori infection in endemically afflicted populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
3
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(95 citation statements)
references
References 38 publications
2
88
3
2
Order By: Relevance
“…In the former case, there was a beneficial cran- berry effect in preventing urinary tract infections [15,16]. In the mixed populations, cranberry consumption significantly increased the eradication of H. pylori compared to placebo [22]. Nevertheless, the eradication rate of cranberry alone was far below that of triple therapy.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the former case, there was a beneficial cran- berry effect in preventing urinary tract infections [15,16]. In the mixed populations, cranberry consumption significantly increased the eradication of H. pylori compared to placebo [22]. Nevertheless, the eradication rate of cranberry alone was far below that of triple therapy.…”
Section: Discussionmentioning
confidence: 95%
“…in a mice model of H. pylori infection caused a significant clearance of the H. pylori mass, but it had no effect on eradicating the pathogen from the gastric lumen [21]. In a randomized controlled study, cranberry juice alone accounted for a 15% of the H. pylori eradication, compared to 5% for placebo [22]. Although this effect in naturally infected humans was significant, the rate of eradication was still considerably lower than that of conventional triple therapy.…”
Section: Introductionmentioning
confidence: 97%
“…Antibacterial adhesion studies demonstrated that in addition to inhibiting E. coli adhesion, cranberry components also inhibit adhesion of H. pylori to human gastric mucus [78]. A randomized, double-blind placebo-controlled trial provided some clinical support for this finding, with significantly lower levels of H. pylori infection observed in adults consuming cranberry juice [79].…”
Section: Helicobacter Pylori Inhibitionmentioning
confidence: 95%
“…However, in vivo studies with garlic (19), jalapeño peppers (20), cinnamon extract (21), broccoli (22), and cranberry juice (23) failed to eradicate H. pylori infection in spite of the wellreported antibacterial data obtained from in vitro experiments. With this concern in mind, researchers have recommended the consumption of these natural foods as chemopreventive agents (6) or in combination with antibiotics to eradicate the bacterial infection (24).…”
Section: Introductionmentioning
confidence: 99%